Effects of Temperature on Time Dependent Rheological Characteristics of Koumiss - Serdal Sabancı; Ömer Çokgezme; Derya Tezcan; Mutlu Cevik; Filiz İçier (Turkish Journal of Agriculture: Food Science and Technology)
The rheological properties of koumiss were investigated at different temperatures (4, 10, and 20°C). Experimental shear stress–shear rate data were fitted to different rheological models. The consistency of koumiss was predicted by using the power-law model since it described the consistency of koumiss best with highest regression coefficient and lowest errors (root mean square error and chi-square). Koumiss exhibited shear thinning behavior (n